ÉTICA NEOPENTECOSTAL E O MUNDO DO TRABALHO: AFINIDADES ELETIVAS ENTRE O NEOPENTECOSTALISMO E O TOYOTISMO NO BRASIL A PARTIR DA DÉCADA DE 1990 - Bandeira, Wesley Silva (2015)
The Pentecostal religious phenomenon has grown considerably in recent years in Brazil, because of that the concern of researchers increases in order to understand its operating logic. The focus of this work is not an isolated studycase , but examining the social context that allows the flourishing of this Christianity aspect. Therefore, I study the relationship between religion and the world of work, assuming that there is an elective affinity between the neo-Pentecostalism and the Toyotism. The study object period focuses on Brazil from the 1990s, this choice occurs by the political and economic changes that the country had and have with the neoliberalism. Nowadays the world of work is characterized by its new productive restructuring, in the transformation of Fordism to the Toyotism, I consider that this change is substantial for recent ways of work. I found that the neo-Pentecostal speech has elective affinity with these metamorphoses giving axiological senses to the current aspects of work. The first chapter approaches the Toyotism in Brazil from the 1990s, highlighting the transformation from Fordism to flexible work. In the second chapter it is highlighted the Pentecostal phenomenon in its contemporary growth and it defines the concepts about religion that guided this research. At last, in chapter three, it shows the relationship between these two areas, the way the neo-Pentecostal ethics is in elective affinities with Toyotism.